Impacts of Climate Change on Rubber Production in Lower Southern Thailand - Thaiburi, Narid; Sinnarong, Nirote; Autchariyapanitkul, Kittawit; Nunthasen, Ke (Princess of Naradhiwas University Journal, 2021)
The objective of this study were to analyze the impacts of climate change on the yield of rubber through model and Ordinary Least Square Method using panel data of 5 provinces in lower southern Thailand. From 1989 to 2019, the analysis showed that the variance of the average temperature elasticity, the elasticity of average rainfall and the rainfall variance resulted in production of yield of rubber with statistical significance. In other words, the level of rainfall changing too fast decreased the yield of rubber tree at 1.00% and resulted in reduction of rubber production at 1.73%. In addition, it was found that when the temperature increased at 1.00%, the yield of rubber dropped at 1.56%. From the model of effect of climate change on rubber production, the result showed that the rubber production received the impact from this situation.